Pengaruh Audit Fee, Time Budget Pressure, Dan Gender Terhadap Kualitas Audit (Studi Pada Auditor Kap Di Kota Malang) - Fabiola Angele Happy Damayanti; Bintang Kusucahyo (Universitas Katolik Widya Karya Malang, 2022)
The purpose of this study examines the impact of audit fees, time budget pressure, and gender on audit quality. Data collection techniques using a questionnaire. This type of explanatory research uses primary data with a population of 73 auditors, the sampling technique using purposive sampling method is 7 KAPs with 45 auditor respondents. The results of the questionnaire were tested through the classical assumption test and multiple linear regression tests. The results of the analysis of audit fees, time budget pressure, and gender have a simultaneous effect on audit quality. Audit fees and time budget pressure have a partial effect on audit quality besides that gender does not affect audit quality. The variable that has the dominant influence on audit quality is time budget pressure.